Kuliah Manajemen di tengah gempuran AI apakah masih relevan? - darmawan, muamal hamdi (Maliki Interdisciplinary Journal, 2026)
The rapid development of Artificial Intelligence (AI) has sparked debate regarding the relevance of formal management education in higher education. Many traditional managerial functions, such as data analysis and routine decision-making, are now being replaced by more efficient automated algorithms. This article aims to explore the extent to which management studies remain relevant in the digital era and the adaptation strategies required to face these changes. Through a qualitative approach and literature study referencing various publications in the UIN Malang Repository, it was found that although AI can automate technical aspects, human elements in management such as ethical leadership, emotional intelligence, and change management remain irreplaceable. The management curriculum needs to transform by integrating digital literacy and humanistic values. The results of the study indicate that management studies remain relevant as long as educational institutions are able to marry technology with moral values, national identity, and inclusive managerial strategies. These findings emphasize that higher education institutions play a role not only as providers of technical competency but also as spaces for developing the character of future managers who are adaptive and possess integrity. The integration of technology-based learning, interdisciplinary approaches, and the strengthening of soft skills are key to preparing management graduates capable of competing in the era of artificial intelligence. Thus, management education is not experiencing a reduction in relevance but is instead undergoing a strategic repositioning as a discipline that balances technological innovation with the social, cultural, and ethical dimensions of modern managerial practice.